PENGEMBANGAN KAWASAN WISATA DANAU PERINTIS SEBAGAI DESTINASI WISATA BERKELANJUTAN BERBASIS SMART TOURISM - Kurniadi Hasan; Fidya Hardiyanti H. Latala; Regi Mokodongan; Misbahudin Djaba; Octaviani Suryaningsih Masaguni (Universitas Bina Taruna Gorontalo, 2024)
This research aims to identify the tourism potential of Perintis Lake and develop it as a sustainable tourism destination smart tourism. In addition, this research was conducted to analyze and evaluate the need for technology and innovation in the management of Lake Perintis-based tourist destinations smart tourism. The approach used in this research is qualitative with descriptive methods. This research uses primary and secondary data sources. Data collection was carried out through observation, interviews, FGD and documentation. The research results show that the Perintis Lake tourist area has the potential to be developed into a superior and sustainable tourist destination. This can be realized by implementing three main components smart tourism ie smart experience, smart business ecosystem And smart destination integrated through implementation smart tourism technology like informativeness, accessibility, interactivity, as well as personalization in its management. From all components smart tourism and smart tourism technology, has not been fully implemented in the management of the Perintis Lake tourist destination. Therefore, it is necessary to accelerate the provision of more adequate ICT infrastructure in its development.